Flood-induced load effects on real-scale structures: a 3D multilevel dynamic analysis (Fracture and Structural Integrity, 2025)
In this work, the structural behavior of masonry buildings under flash flood actions is analyzed by using a novel 3D multilevel fluid/structure model. The proposed numerical framework consists of a macro-scale model based on the computational fluid dynamic, able to simulate the dynamic free-stream flow of a fluid impacting rigid solids and a meso-scale structural model that employs a coupled damage-plasticity approach to describe the nonlinear behavior of the masonry buildings, subjected to the fluid dynamic pressure extracted by the macro-scale fluid analysis. The integrated model was employed to assess the fluid-structure interaction effects on the global structural response, in terms of load-carrying capacity and damage patterns, of a real-scale masonry structure subjected to flood-induced loading conditions. Finally, a parametric analysis is performed in order to understand the influence of the fluid inlet velocity and water depth on the failure mechanisms of the structure. The results highlight the good numerical capabilities of the proposed multilevel model, establishing it as a valuable numerical tool for the structural vulnerability assessments under flood actions.
Keywords: 3D Finite element analysis; Coupled damage-plasticity approach; Masonry structure; Flash floods